Ciência e religião: reflexões acerca da abordagem de temas controversos pelo professor de ciências nos anos iniciais - Sanches, Fabiane (2017)
The relations between Science and Religion in society and the possibilities of dialogue among them aiming at the construction of knowledge, are themes that still generate many controversies within educational institutions. The obstacles, in general, are product of a school system that has been characterized by the search for scientific rigor that is often not demystified in the school, constituting itself as an absolute and undeniable truth. Such situation tends to provoke confrontation of ideas, especially when themes that present cultural, philosophical and religious explanations are debated. In this scenario the positioning assumed by the teacher in the classroom is notable. Understanding, therefore, some of the factors that influence the development of scientific and religious knowledge, throughout the History of humanity is of fundamental importance for the task of teaching and learning. In this research we focus mainly on the relevance of reflecting the History of Science as one of the essential instruments to combat the cultural shocks that are established between the previous knowledge brought by the students to the classroom, facing the new knowledge that tend to form, also by means of the curricular contents. In this perspective, the defense is that there is no need to deny personal beliefs - in addition to the questions of science - neither by the teachers nor by the students, regarding the controversial contents, avoiding the formation of epistemological obstacles on teaching and learning science. Given this context, the study aims to investigate the connections and conflicts between science and religion in the early years of elementary school in the city of Cascavel - PR, Brazil, and whether the network teachers' approach has contributed to the perspective of dialogue between Scientific explanations and religious explanations in the themes Origin and Evolution. The dissertation is consisted on three distinct moments of studies: bibliographic research, document research and field research. The bibliographic research dealt with the reading and analysis of articles, dissertations, theses and scientific publications in general, concerning the teaching of Sciences, the new proposals for this teaching in recent years and the performance of teachers in subjects related to Science and Religion in the initial years and in other teaching modalities. The document research was based on the mapping and analysis of national, state and municipal educational laws, which regulate the teaching of Sciences, having as a guiding axis the Curriculum for the “Rede Pública Municipal” (Municipal Public Network) - Initial Years. The empirical data were collected through the field research, including interviews recorded in audio, performed with teachers from the 4th and 5th years of elementary school. These two stages of teaching were chosen because they represent a space that the content of the Origin of Life and Evolution of the Human Species are discussed, since the document organizes such subjects in the Matter and Energy axis. In this research, a large number of teachers pointed out that these themes are considered difficult to approach, they also mention the lack of initial training, continuing education and a gap of referrals from the curriculum. However, there are records of reports indicating, in some cases, the valuation of previous conceptions as a starting point in controversial debates. This shows the insertion of dialogical bridges between scientific knowledge and religious knowledge. These evidences were confirmed by the analysis of the data collected.